Aspirations of Sub-State Actors in Sport: A Study of Quebec Paradiplomacy through the Instrument of Football - Dermawan, Windy; Fadel, Mohamad; Sudirman, Arfin; Santoso, Rizal Budi (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2024)
Quebec is a sub-state actor active in carrying out paradiplomacy in various fields. This is supported by Canada’s federal state form, which gives its constituent actors the freedom to conduct foreign relations freely. The dynamics of Quebec paradiplomacy are not only in the context of trade and investment but also in political aspects related to identity. Quebec is a sub-state actor whose citizens are predominantly French-Canadian (Quebecois). The desire to gain recognition for its identity as Quebecois makes Quebec active in carrying out paradiplomacy by participating in soccer in CONIFA. Entities in Quebec have fought for their identity as Quebecois through the self-determination movement. The purpose of this research is to analyze the efforts made by Quebec to show the existence of its identity abroad through paradiplomacy in the field of soccer. The research method used is qualitative, collecting data through interviews with several relevant sources, internet based studies, document tracking, and archives related to the research problem. This research shows that soccer has become one of the instruments Quebec uses to show its existence and identity as Quebecois to the global public. Although Quebec’s activities are no longer to pursue independence from Canada, Quebec uses football to promote the achievement of interests in other areas, such as economics and socio-culture. Keywords: Identity, Paradiplomacy, Football, Sub-state, Quebec Quebec merupakan aktor sub-negara yang sangat aktif melakukan paradiplomasi di berbagai bidang. Hal ini didukung oleh bentuk negara federal dari Kanada yang memberikan aktor konstituennya untuk melakukan hubungan luar negeri secara leluasa. Dinamika paradiplomasi Quebec tidak hanya dalam konteks perdagangan dan investasi, tetapi juga pada aspek politik yang terkait dengan identitas. Quebec sebagai aktor sub-negara yang mayoritas warganya Prancis-Kanada (Quebecois). Keinginan untuk mendapatkan pengakuan terhadap identitasnya sebagai Quebecois inilah yang menjadikan Quebec aktif dalam melaksanakan paradiplomasi melalui keikutsertaannyadalam olahraga sepakbola dalam CONIFA. Bahkan, entitas di Quebec pernah memperjuangkan identitas sebagai Quebecois melalui gerakan self-determination. Tujuan dari riset ini adalah menganalisis upaya-upaya yang dilakukan oleh Quebec untuk menunjukkan eksistensi identitasnya di luar negeri melalui paradiplomasi di bidang olahraga sepakbola. Metode riset yang digunakan adalah kualitatif dengan mengumpulkan data melalui wawancara terhadap sejumlah narasumber yang relevan, studi berbasiskan internet, pelacakan dokumen dan arsip yang terkait dengan masalah riset. Riset ini menunjukkan bahwa olahraga sepakbola telah menjadi salah satu instrumen bagi Quebec untuk menunjukkan eksistensi dan identitasnya sebagai Quebecois terhadap publik global. Meskipun kegiatan Quebec ini bukan lagi untuk mengejar kemerdekaan dari Kanada, Quebec menggunakan instrumen sepakbola untuk promosi dalam pencapaian kepentingan di bidang lain, seperti ekonomi dan sosial budaya. Kata-kata Kunci: Identitas, Paradiplomasi, Sepakbola, Sub-negara, Quebec.